Funcionalidade e fatores ambientais que influenciam o nível de atividade física da pessoa com deficiência física em Belém e Manaus - CAMPOS, Jamylle Silva (Universidade Federal do Pará, 2024)
The potentiation of functional capacity occurs through the insertion of the individual in physical activity, generating positive impacts on independence, autonomy, quality of life, functionality, self-esteem, social participation and greater health care, however there are facilitating factors and barriers. Objective: To identify the environmental, functional factors and level of physical activity of people with physical disabilities in rehabilitation and sports centers in the Northern Region. Method: Performed in a motor program for people with disabilities in the city of Manaus-Amazonas and at a Rehabilitation Center in Belém-Pará. Individuals with physical disabilities, of congenital or acquired origin, of both sexes, aged between 18 and 60 years, who performed physical and/or sports activity for at least 6 months, participated of this study. Where sociodemographic data were collected and three questionnaires were applied, namely: WHODAS 2.0, Physical Activity Scale for People with Physical Disabilities (PASIPD) and Measure of the Quality of the Environment (MQE). The sample consisted of 41 participants, which 61% were male, with a mean age of 43,1 (±13,1) years, mean time of injury 17,0 (±12,8) years, single, with income only social benefits or retirement, had completed high school and 26,8% had a diagnosis of spinal cord injury. All data were processed in the jamoviproject 2021 Software (version 2.2), applying the Shapiro-Wilk normality test and Pearson's Linear correlation test. Result: Regarding functionality, there was a predominance of mild difficulty in relation to cognition, self-care, interpersonal relationships, activity of daily living and participation. Noting that the mobility domain was the only one with moderate difficulty. Considering a level of metabolic equivalent physical activity below 30 MET/h/day. There was a correlation between domains related to functionality and environmental factors barriers, but there was no connection between functionality, level of physical activity and facilitating environmental factors. Conclusion: The barrier factors present in the daily lives of people with physical disabilities directly impact functionality, in the aspect of self-care, interpersonal relationships, mobility, activity of daily living and participation.